PELATIHAN PENYUSUNAN BIAYA PRODUKSI DALAM PENENTUAN HARGA POKOK PRODUKSI PADA HOME INDUSTRY KECAP TOP - Ika Kartika; Gytha Nurhana Dhea Praadha Gitama; Dessy Kumala Dewi; Kusnul Khotimah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Micro, small, and medium enterprises (MSMEs) still face challenges in systematically preparing production costs as a basis for determining the cost of goods manufactured (COGM). Home Industry Kecap Top in Cirebon Regency is one of the enterprises that has not yet calculated COGM accurately and still sets selling prices based on estimation. This community service activity aims to enhance partners’ capabilities in preparing production costs and calculating COGM through practice-based training. The method employed is Participatory Action Research (PAR), consisting of observation, training, mentoring, and evaluation stages. The results indicate an improvement in partners’ understanding of identifying production cost components and calculating COGM using the full costing method. The calculation shows that the COGM of Kecap Top is IDR 19,808 per unit. This training encourages more accurate and sustainable selling price determination.